A simplified algorithm for measuring erythrocyte deformability dispersion by laser ektacytometry. (31st August 2015) - Nikitin, S Yu; Yurchuk, Yu S
Abstract The possibility of measuring the dispersion of red blood cell deformability by laser diffractometry in shear flow (ektacytometry) is analysed theoretically. A diffraction pattern parameter is found, which is sensitive to the dispersion of erythrocyte deformability and to a lesser extent – to such parameters as the level of the scattered light intensity, the shape of red blood cells, the concentration of red blood cells in the suspension, the geometric dimensions of the experimental setup, etc. A new algorithm is proposed for measuring erythrocyte deformability dispersion by using data of laser ektacytometry.